Neurodidactics In Teaching Foreign Languages (Texas Journal of Multidisciplinary Studies, 2021)
In this article, the term "neurodidactics" is used as a way of interpreting the process of teaching foreign languages from the point of view of neurosciences. Neuroscience is a relatively new term that combines methods and directions that study the brain: how it works and how it works. From a neurobiological point of view, learning is the formation of populations of neurons in the cerebral cortex. Each person already comes to this world, possessing about 100 billion neurons, weakly connected to each other. As the child gradually learns, "chaotic" neurons connect to neural networks.